Affective dysregulation in children is associated with difficulties in response control in emotional ambiguous situations - Giller, Franziska; Aggensteiner, Pascal; Banaschewski, Tobias; Döpfner, Manfred; Brandeis, Daniel; Rößner, Veit; Beste, Christian (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2022)
Background - Affective dysregulation (AD), or synonymously "irritability", is a transdiagnostic construct that serves as a diagnostic criterion in various childhood mental disorders. It is characterized by severe or persistent outbursts of anger and aggression. Emotional self-regulation is highly dependent on the ability to process relevant and ignore conflicting emotional information. Understanding neurophysiological mechanisms underlying impairment in AD may provide a starting point for research on pharmacological treatment options and evaluation of psychotherapeutic intervention. - Methods - A total of 120 children 8 to 12 years of age (63 with AD and 57 typically developing) were examined using an emotional Stroop task. Signal-decomposed electroencephalographic recordings providing information about the affected sensory-perceptual, response selection, or motor information processing stage were combined with source localization. - Results - Behavioral performance revealed dysfunctional cognitive-emotional conflict monitoring in children with AD, suggesting difficulties in differentiating between conflicting and nonconflicting cognitive-emotional information. This was confirmed by the electroencephalographic data showing that they cannot intensify response selection processes during conflicting cognitive-emotional situations. Typically developing children were able to do so and activated a functional-neuroanatomical network comprising the left inferior parietal cortex (Brodmann area 40), right middle frontal (Brodmann area 10), and right inferior/orbitofrontal (Brodmann area 47) regions. Purely sensory-perceptual selection and motor execution processes were not modulated in AD, as evidenced by Bayesian analyses. - Conclusions - Behavioral and electroencephalogram data suggest that children with AD cannot adequately modulate controlled response selection processes given emotionally ambiguous information. Which neurotransmitter systems underlie these deficits and how they can be improved are important questions for future research.
Gesehen am 21.03.2023